ANALISIS KETERLAKSANAAN STANDAR PENANGANAN BAHAN HEWANI SEAFOOD UNTUK MENJAGA KUALITAS PANGAN DI BUTCHER SECTION AEROFOOD ACS SURABAYA - Novi Nur Masitho; Niken Purwidiani; Qorry' Aina; Andika Kuncoro Widagdo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the handling process of seafood raw materials at the Butcher Section of Aerofood ACS Surabaya, which includes preparation, cutting, and storage. Proper seafood handling is crucial in the airline catering industry as it directly relates to quality, safety, and food suitability. This study adopts a descriptive qualitative approach with data collection methods through direct observation, in-depth interviews, and documentation. The results show that the preparation process utilizes thawing in a thawing room at 5–10°C for 10–12 hours until the product temperature reaches ≤8°C, along with the implementation of hygiene through re-washing of seafood. The cutting process uses large/small knives and blue cutting boards with chlorin sanitation at 50–100 ppm, and all seafood must be thawed beforehand. For storage, a complete labeling system with different colors each day is applied for FIFO implementation, with storage in chiller (0–5°C) at 1×24 hours shelf life and freezer (-18°C) with approximately 6 months shelf life. However, this study also identifies several problems that need to be addressed, such as material loss during thawing of 15–50% The drip loss varies among seafood types, with milkfish showing approximately 5%, shellfish around 5%, shrimp around 5%, dory fish about 10–15%, and squid reaching up to 50% and suboptimal uniformity of seafood weight and size. This study provides recommendations for improving operational standards in seafood handling at the Butcher Section.